Pengaruh pijat bayi terhadap durasi menyusu neonatus di wilayah kerja Puskesmas Kibin Kabupaten Serang - Putri, Dian Priharja; Yuningsih, Sukarni Setya (Indonesia Berdaya, 2023)
Exclusive breastfeeding protects infants against harmful diseases and strengthens the bond between mother and child. To reduce child morbidity and mortality, it is recommended that children be fed only with breast milk for at least 6 months. As many as 31.36% of the 37.94% of sick children in Indonesia do not receive exclusive breastfeeding. Exclusive breastfeeding also prevents stunting and contributes to reducing the risk of obesity and chronic diseases. For this reason, it is important to make efforts so that mothers are able to provide maximum breastfeeding. This research is a pre-experimnetal design with control group design. The sample was 50 breastfeeding mothers who have neonates (0-30 days old) in the working area of Kibin Community Health Center, Serang Regency in October 2023. Analysis using T-Indepent test with SPSS 27.0. There was no difference in the average duration of breastfeeding on day 10 (5.44 minutes) and day 20 (5.52 minutes) in the group that did not do baby massage. While in the group that did baby massage there was an increase in the average duration of breastfeeding on day 10 (5.40 minutes) and day 20 (7.36 minutes). The result of t-test obtained p-value = 0.00 (less than 0.05) means statistically shows that infant massage has an influence on the duration of breastfeeding in neonates in the working area of Kibin Health Center, Serang Regency. Infant massage has an influence on breastfeeding duration of neonates in the working area of Kibin Health Center, Serang Regency